An investigation into teachers' correction and its effects on non-English majored students' motivation and improvement in learning pre-ESP subject at Viettronics Technology College = Tìm hiểu việc sửa lỗi của giáo viên và ảnh hưởng của nó đối với hứng thú - Nguyễn, Thị Hồng Luyến (ĐHNN, 2017)
43 p. + CD-ROM